Role–Playing Activities: Essential Tools for Enhancing English Proficiency to Thai Primary Students - Tambunan, Putri Al Shifa; Kharisma, Adib Jasni; Syahputri, Diani (Universitas Pahlawan Tuanku Tambusai, 2025)
This study looks at how well role-playing exercises improve English proficiency among Thai primary pupils, with an eye toward speaking abilities, self-confidence, and attitudes about English. Data were gathered by means of speaking tests both before and after running role-playing activities using a Classroom Action Research (CAR) approach. Students' speaking skills showed a notable improvement; the average proficiency score rose from 57.5 in Cycle 1 to 68.13 in Cycle 2. Furthermore, the proportion of students reaching the minimal speaking score of 65 changed from 50% in Cycle 1 to 81.25% in Cycle 2. These findings underline the need for using interactive teaching strategies, including role-playing, to close the gap between theoretical knowledge and practical application, thereby improving English communication abilities among students.